Enantioselective Palladium-Catalyzed Diamination of Alkenes Using N‑Fluorobenzenesulfonimide - Ingalls, Erica L; Sibbald, Paul A; Kaminsky, Werner; Michael, Forrest E (Journal of the American Chemical Society, 2013)
An enantioselective Pd-catalyzed vicinal diamination of unactivated alkenes using N-fluorobenzenesulfonimide as both an oxidant and a source of nitrogen is reported. The use of Ph-pybox and Ph-quinox ligands afforded differentially protected vicinal diamines in good yields with high enantioselectivities. Mechanistic experiments revealed that the high enantioselectivity arises from selective formation of only one of four possible diastereomeric aminopalladation products of the chiral Pd complex. The aminopalladation complex was characterized by X-ray crystallography.